PENEGAKAN HUKUM TERHADAP TINDAK PIDANA DI BIDANG CUKAI HASIL TEMBAKAU DI WILAYAH HUKUM KANTOR PENGAWASAN DAN PELAYANAN TIPE MADYA PABEAN B MAKASSAR - Talib, Abdul (Al-Hikmah, 2019)
The research was conducted and aimed at: 1) To determine the law enforcement of tobacco product excise crimes carried out by the Office of Supervision and Service of the Medium Type of Customs B Makassar; 2) To find out what are the obstacles in the enforcement of excise tax on tobacco products faced by the Office of Supervision and Service of the Medium Type of Customs B Makassar.This type of research is empirical legal research, namely legal research that examines the implementation or implementation of positive legal provisions (legislation) factually on any particular legal event that occurs in society. The legal material used consists of primary legal data and secondary legal data. Techniques for collecting legal data are collected through literature studies and field studies. Then the technique for analyzing with qualitative analysis techniques by sorting and selecting, classifying, and connecting the realities that occur in the field with the problems studied, so as to provide a clear picture of what happened in the field so that it comes to a conclusion.The results showed that: 1) the law enforcement of tobacco product excise carried out by the Office of the Supervision and Service of the Medium Type of Customs B Makassar has been running optimally, this can be seen from the number of prosecution carried out by investigators of the Civil Service Office of the Type of Control Pabean B Makassar from 2017 there were 14 cases and all received sanctions both criminal and administrative and in 2018 a number of 8 cases also received criminal and administrative sanctions; 2) the constraints in the enforcement of tobacco product excise crimes faced by the Office of Supervision and Service of the Type of Customs of Bab Makassar are the lack of resources for investigating civil servants as well as a lack of socialization to the public regarding the excise crime of tobacco products.